(1/2x-3)(4x-1/3)
3 answers
what do you want us to do with this equation?????
It is not an equation, it is an algebraic expression.
You could get rid of the fractions by multiplying by 6/6
(1/2x-3)(4x-1/3)
= (1/2x-3)(4x-1/3) * 6/6
= (3x - 18)/(24x - 2)
= 3(x - 6)/(2(12x - 1)) , (don't know if that looks any more simplified)
You could get rid of the fractions by multiplying by 6/6
(1/2x-3)(4x-1/3)
= (1/2x-3)(4x-1/3) * 6/6
= (3x - 18)/(24x - 2)
= 3(x - 6)/(2(12x - 1)) , (don't know if that looks any more simplified)
(1/2x-3)(4x-1/3).
2x^2 - 1/6x - 12x + 1,
2x^2 - 73/6x + 1.
2x^2 - 1/6x - 12x + 1,
2x^2 - 73/6x + 1.